Comparison of RT-PCR, RT-LAMP, and Antigen Quantification Assays for the Detection of SARS-CoV-2 - Tanimoto, Yoshihiko; Mori, Ai; Miyamoto, Sonoko; Ito, Erika; Arikawa, Kentaro; Iwamoto, Tomotada (Japanese Journal of Infectious Diseases, 2022)
A rapid and simple alternative test to real-time reverse transcription-polymerase chain reaction (RT-PCR) is required for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to help curb the spread of coronavirus disease (COVID-19). In the present study, we compared the RT-PCR method with chemiluminescent enzyme immunoassay (CLEIA) and reverse transcription loop-mediated isothermal amplification (RT-LAMP). We observed that the number of SARS-CoV-2 RNA copies and the CLEIA antigen quantification values were highly correlated. The detection limit for antigen quantification was 42.8 RNA copies for saliva samples and 23.4 copies for nasopharyngeal swab samples. For both purified RNA and purification-free crude RNA, the number of RNA copies and RT-LAMP threshold time (Tt) values were inversely correlated. RT-LAMP with purified RNA detected low copy numbers of RNA (5–50 copies), whereas fewer than 250 RNA copies could not be detected using crude RNA. CLEIA antigen quantification is potentially useful for large-scale screening, as it is compatible with high-throughput testing. RT-LAMP with crude RNA samples is applicable for rapid point-of-care testing because it can directly use patient specimens. It is important to select a diagnostic method that is simple and rapid when compared with RT-PCR, depending on the situation.